Long-term accumulation of uranium in bones of Wistar rats as a function of intake dosages - Arruda-Neto, JDT; Guevara, MVM; Nogueira, G. P.; Saiki, M.; Cestari, A. C.; Shtejer, K.; Deppman, A.; Pereira, J. W.; Garcia, F.; Geraldo, L. P.; Gouveia, A. N.; Guzman, F.; et al. (Oxford University Press, 2004)
Groups of Wistar rats were fed with ration doped with uranyl nitrate at concentration A ranging from 0.5 to 100 ppm, starting after the weaning period and lasting until the postpuberty period when the animals were sacrificed. Uranium in the ashes of bones was determined by neutron activation analysis. It was found that the uranium concentration in the bones. as a function of A, exhibits a change in its slope at similar to20 ppm-a probable consequence of the malfunctioning of kidneys. The uranium transfer coefficient was obtained and an analytical expression was fitted into the data. thus allowing extrapolation down to low doses. Internal and localized doses were calculated. Absorbed doses exceeded the critical dose. even for the lowest uranium dosage.